A link between the driver mutations and dysregulated apoptosis in BCR-ABL1 negative myeloproliferative neoplasms. Issue 4 (3rd July 2016) - Mambet, Cristina; Matei, Lilia; Necula, Laura Georgiana; Diaconu, Carmen C.
ABSTRACT: The current understanding of BCR-ABL1 negative myeloproliferative neoplasms pathogenesis is centred on the phenotypic driver mutations in JAK2, MPL, or CALR genes, and the constitutive activation of JAK-STAT pathway. Nonetheless, there is still a need to better characterize the cellular processes that are triggered by these genetic alterations, such as apoptosis that might play a role in the pathological expansion of the myeloid lineages and, especially, in the morphological anomalies of the bone marrow megakaryocytes. In this article we will explore the connection between the driver mutations in MPN and the abnormal apoptosis that might be translated in new therapeutic strategies.